Dibenzodiazepinone-type muscarinic receptor antagonists conjugated to basic peptides: Impact of the linker moiety and unnatural amino acids on M2R selectivity - Weinhart, Corinna G.; Wifling, David; Schmidt, Maximilian; Neu, Eduard; Höring, Carina; Clark, Timothy; Gmeiner, Peter; Keller, Max (European Journal of Medicinal Chemistry, 2021)
The family of human muscarinic acetylcholine receptors (MRs) is characterized by a high sequence homology among the five subtypes (M1R-M5R), being the reason for a lack of subtype selective MR ligands. In continuation of our work on dualsteric dibenzodiazepinone-type M2R antagonists, a series of M2R ligands containing a dibenzodiazepinone pharmacophore linked to small basic peptides was synthesized (64 compounds). The linker moiety was varied with respect to length, number of basic nitrogens (0–2) and flexibility. Besides proteinogenic basic amino acids (Lys, Arg), shorter homologues of Lys and Arg, containing three and two methylene groups, respectively, as well as D-configured amino acids were incorporated. The type of linker had a marked impact on M2R affinity and also effected M2R selectivity. In contrast, the structure of the basic peptide rather determined M2R selectivity than M2R affinity. For example, the most M2R selective compound (UR-CG188, 89) with picomolar M2R affinity (pKi 9.60), exhibited a higher M2R selectivity (ratio of Ki M1R/M2R/M3R/M4R/M5R: 110:1:5200:55:2300) compared to the vast majority of reported M2R preferring MR ligands. For selected ligands, M2R antagonism was confirmed in a M2R miniG protein recruitment assay.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Basic amino acid; Dibenzodiazepinone derivative; Induced-fit docking; M2R antagonist; M2R selectivity; MR subtype selectivity; Muscarinic acetylcholine receptors; Peptide